GABA-Ergic Dysfunction in Succinic Semialdehyde Dehydrogenase Deficiency - J Gordon Millichap (Pediatric Neurology Briefs, 2012)
Investigators at the Clinical Epilepsy and Neurorehabilitation Sections, NIH, Bethesda, MD; Albert Ludwigs University, Freiberg, Germany; and Children's National Medical Center, Washington, DC used transcranial magnetic stimulation (TMS) to quantify the excitation and inhibition in primary motor cortex in 8 patients (mean age 15.4 years) with succinic semialdehyde dehydrogenase (SSADH) deficiency.